Some Cytokines Levels (IL-6 and IL-10) in Sera Patients with Cutaneous Leismanasis in Nassiriya Province - Alaa Hussein Oleiwi (University of Thi-Qar Journal of Science, 2020)
The present study was carried out in the Labs of collage of education for pure science, during period from January 2017 to endDecember of the same year. The immune status investigates for CLpatients by measuring the levels of cytokines (IL6and IL10) in sera using a technique enzyme-linked immune Sorbent adsorptive (ELISA). The study included 120 subjects with (60 CLpatientsL.majar and 60 CLpatients L. tropica with and (30) were healthy control. Increased mean Serum level of IL6 was in the observed in the total patients as compared to control Subjects (224.53pg/ml,70.70pg/ml), the result indicate there was significant difference at (p<0.05) ,such observation was consistent in the patient infected with L.majar and L. tropica (104 .90 pg/ml and 112.78 pg/ml) respectively. The results of the IL10 showed significant difference at (p<0.05)increased of mean Serum level in the total CL patients as compared to control Subjects(226.90 pg/ml 46.77pg/ml,).Ahighly significant difference at (p<0.05) increased observed in patients group infected with L.majar and followed by patients group infected L. tropica (112.78pg/ml and 114.12pg/ml) respectively.These results revealed that the excessive presence of cytokines might play a role in CL patients.